Konsep Kurikulum dan Materi Pendidikan Islam:: Perspektif Alquran-Hadis Serta Implementasinya dalam Taksonomi Bloom - Ade Muhammad Ritonga (ASSUNNAH PRESS, 2025)
Education requires a curriculum as the main instrument for achieving learning objectives. The curriculum is not static, but can change line with developments in educational needs. This study aims to examine the basic concepts of curriculum, particularly the Islamic education curriculum, and its implementation within the framework of Bloom's taxonomy. The study employs a literature review method with a textual analysis approach to relevant literature, such as scientific journals, academic books, and previous research findings. Data were analyzed using content analysis techniques to extract key ideas from the available sources. The results of the study indicate that the Islamic education curriculum refers to authentic sources, namely the Qur'an and Hadith, and must be integrated with the values of Islamic teachings. This curriculum possesses comprehensive and holistic characteristics, taking into account the overall development of students, while also considering individual differences in terms of needs, interests, and abilities. The curriculum material covers tauhid (monotheism), iman (faith), ihsan (benevolence), akhlak (morality), as well as science and mathematics. All of this material needs to be integrated into Bloom's three taxonomic domains: cognitive, affective, and psychomotor. These findings emphasize the importance of adaptive and integrated Islamic education curriculum design in shaping students' character and competencies holistically.